Green spaces and General Health: Roles of mental health status, social support, and physical activity. (May 2016) - Dadvand, Payam; Bartoll, Xavier; Basagaña, Xavier; Dalmau-Bueno, Albert; Martinez, David; Ambros, Albert; Cirach, Marta; Triguero-Mas, Margarita; Gascon, Mireia; Borrell, Carme; Nieuwenhuijsen, Mark J.
Abstract: Green spaces are associated with improved health, but little is known about mechanisms underlying such association. We aimed to assess the association between greenness exposure and subjective general health (SGH) and to evaluate mental health status, social support, and physical activity as mediators of this association. This cross-sectional study was based on a population-based sample of 3461 adults residing in Barcelona, Spain (2011). We characterized outcome and mediators using the Health Survey of Barcelona. Objective and subjective residential proximity to green spaces and residential surrounding greenness were used to characterize greenness exposure. We followed Baron and Kenny's framework to establish the mediation roles and we further quantified the relative contribution of each mediator. Residential surrounding greenness and subjective residential proximity to green spaces were associated with better SGH. We found indications for mediation of these associations by mental health status, perceived social support, and to less extent, by physical activity. These mediators altogether could explain about half of the surrounding greenness association and one-third of the association for subjective proximity to green spaces. We observed indications that mental health and perceived social support might be more relevant for men and those younger than 65 years. The results for objective residential proximity to green spaces were not conclusive. In conclusion, our observed association between SGH and greenness exposure was mediated, in part, by mental health status, enhanced social support, and physical activity. There might be age and sex variations in these mediation roles. Highlights: Mechanisms underlying health benefits of green spaces are not established. Residential surrounding greenness is associated with better general health. Subjective residential proximity to green spaces is associated with better general health. Mental health, social support, and physical activity mediated these associations. Objective residential proximity to green spaces did not influence general health.